Factores psicológicos asociados a intentos de suicidio en jóvenes entre 16-25 años del Valle de Aburrá (2009)
ABSTRACT: This research shows the presence of psychological factors like hopelessness, low levels of self-efficacy, and personality traits on young people between 16 and 25 years from the Aburrá Valley with suicide attempts. For this research twenty four (20 women, 4 men) patients that had attempted to commit suicide were evaluated. For this research it were applied some instruments like The Millon Index of Personality (MIPS™) (Millón, 1997), The Beck Hopelessness Scale (BHS) (Beck & Steer, 1988), The Self-efficacy Test, and a semi-structured interview. It was found a general personality profile characterized by the presence of individual elements, discrepancy, unhappiness and sociability. The personality profile was analyzed also by the Frequency distribution of the three tasks of the MIPS™. On the motivational goals area two components dominated, individuality and preservation; on the cognitive means area dominated the component innovation; and in the area interpersonal behavior dominated the components discrepancy, discontent, and sociability.